Fatty acid composition of vegetable marrows and zucchini leaves - Olena O. Iosypenko; Viktoriia S. Kyslychenko; Zinaida I. Omelchenko; Iryna S. Burlaka (Pensoft Publishers, 2019)
The qualitative composition and quantitative content of fatty acids in leaves of vegetable marrows (Cucurbita pepo L. var. giromontina Alef.), zucchini (Cucurbita pepo L. var. cylindrica Paris) yellow- and green-fruits varieties were determined by using GC/MS. 14 fatty acids were identified as the result of the experiment. Unsaturated fatty acids were found to be dominated in the raw plant material. The total content of unsaturated fatty acids amounted to 60.47% in vegetable marrows leaves, 64.35% yellow zucchini leaves and 68.85% green zucchini leaves, among which linoleic and linolenic acid dominated. The related health lipid indices (IA, atherogenicity, IT, thrombogenicity and IH, health) were determined. It is shown that the use of such biological resources is actual and expedient for the purpose of alimentary correction of the physiological condition of a person.